Australian children and adolescents with gender dysphoria: Clinical presentations and challenges experienced by a multidisciplinary team and gender service. Issue 1 (1st February 2021) - Kozlowska, Kasia; McClure, Georgia; Chudleigh, Catherine; Maguire, Ann M; Gessler, Danielle; Scher, Stephen; Ambler, Geoffrey R
This prospective study examines the clinical characteristics of children ( n = 79; 8.42–15.92 years old; 33 biological males and 46 biological females) presenting to a newly established, multidisciplinary Gender Service in New South Wales, Australia, and the challenges faced by the clinicians providing clinical services to these patients and their families. The clinical characteristics of the children were comparable to those described by other paediatric clinics providing gender services: a slight preponderance of biological females to males (1.4: 1); high levels of distress (including dysphoria about gender), suicidal ideation (41.8%), self-harm (16.3%), and suicide attempts (10.1%); and high rates of comorbid mental health disorders: anxiety (63.3%), depression (62.0%), behavioural disorders (35.4%), and autism (13.9%). The developmental stories told by the children and their families highlighted high rates of adverse childhood experiences, with family conflict (65.8%), parental mental illness (63.3%), loss of important figures via separation (59.5%), and bullying (54.4%) being most common. A history of maltreatment was also common (39.2%). Key challenges faced by the clinicians included the following: the effects of increasingly dominant, polarized discourses on daily clinical practice; issues pertaining to patient and clinician safety (including pressures to abandon the holistic [biopsychosocial] model); the difficulties of untangling gender dysphoria from comorbid factors such as anxiety, depression, and sexual abuse; and the factual uncertainties present in the currently available literature on longitudinal outcomes. Our results suggest the need to bring into play a biopsychosocial, trauma-informed model of mental health care for children presenting with gender dysphoria. Ongoing therapeutic work needs to address unresolved trauma and loss, the maintenance of subjective well-being, and the development of the self.